Diversity of Terrestrial Snails in Dien Bien Province (Mollusca: Gastropoda) - Sang, Do Duc (VNU Journal of Science: Natural Sciences and Technology, 2021)
The research has been carried out in Dien Bien Province (Northwest region of Vietnam) from 2013 to 2019. This is the very first checklist of the terrestrial snails of Dien Bien Province. The checklists provide databases and helps to understand the biodiversity richness of the particular region of country. As such, they also open trends for further research priorities. Altogether 80 species and subspecies of terrestrial snails belonging to 17 families, 49 genera are listed with 5 genera ( Lagocheilus, Metalycaeus, Scabrina, Laotia , and Moellendorffia ) and 36 new species recorded for Dien Bien Province